2019
DOI: 10.1016/j.neubiorev.2019.01.018
|View full text |Cite
|
Sign up to set email alerts
|

The auditory cortex and the emotional valence of sounds

Abstract: How and where sensory stimuli, such as tones or lights, are linked to valence is an important unresolved question in the field of neuroscience. The auditory cortex is essential to analyse the identity and the behavioural importance of tones paired with emotional events. On the contrary, whether the auditory cortex may also encode information on the emotional-motivational valence of sounds is much more controversial. Here, we reviewed recent studies showing that the activity of cortical neurons reflects informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 69 publications
(89 reference statements)
1
38
0
1
Order By: Relevance
“…The auditory cortex (AC), for example, plays an important role in sound analysis and even in coordinating acoustically guided behaviors (Song et al, 2010;Li et al, 2017). Neuronal activity within the AC represents a large range of acoustic properties including spectrotemporal structure (Gaese and Ostwald, 1995;Lu et al, 2001Lu et al, , 2016Yin et al, 2011;Gaucher et al, 2013;Kanold et al, 2014;Gao and Wehr, 2015;Martin et al, 2017;Sheikh et al, 2019), sound source location encompassing azimuth/elevation coding (Recanzone, 2000;Mrsic-Flogel et al, 2005;Salminen et al, 2015;Trapeau and Schonwiesner, 2018) and target distance processing (Suga and O'Neill, 1979;Hechavarria et al, 2013;Bartenstein et al, 2014;Beetz et al, 2016), as well as abstract properties, such as sound "emotional valence" (Concina et al, 2019) and future behavioral outcomes based on auditory stimuli (Francis et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The auditory cortex (AC), for example, plays an important role in sound analysis and even in coordinating acoustically guided behaviors (Song et al, 2010;Li et al, 2017). Neuronal activity within the AC represents a large range of acoustic properties including spectrotemporal structure (Gaese and Ostwald, 1995;Lu et al, 2001Lu et al, , 2016Yin et al, 2011;Gaucher et al, 2013;Kanold et al, 2014;Gao and Wehr, 2015;Martin et al, 2017;Sheikh et al, 2019), sound source location encompassing azimuth/elevation coding (Recanzone, 2000;Mrsic-Flogel et al, 2005;Salminen et al, 2015;Trapeau and Schonwiesner, 2018) and target distance processing (Suga and O'Neill, 1979;Hechavarria et al, 2013;Bartenstein et al, 2014;Beetz et al, 2016), as well as abstract properties, such as sound "emotional valence" (Concina et al, 2019) and future behavioral outcomes based on auditory stimuli (Francis et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a growing body of research indicates that it is not the physical properties of sound, but the message conveyed within the sound that leads to different emotions. For instance, a related study found that auditory cortex would encode information on the emotional-motivational valence of sounds so that people could recognize sound as aversive or pleasant [23]. Therefore, using emotional sounds in a soundscape design is an effective way to regulate emotion.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, A2 may work in cooperation with the amygdala to associate affective information with auditory information after it receives auditory information from primary fields via the corticocortical pathways 50,51 . A recent study using rats suggested that value-coding neurons exist in parts that correspond to those located near mouse A2 52,53 , which may be evidence of the La–A2 feedback pathways. It is possible that A2 works to provide biological meaning for emotion-arousing sounds such as conspecific courtship songs and predatory calls, and thus plays a more important role in signal processing than simple sound analysis.…”
Section: Discussionmentioning
confidence: 99%